Formação docente: conhecimento do conteúdo específico. Se eu não entendo, como posso explicar? - Teixeira Júnior, José Gonçalves (2007)
This study had as purpose to investigate and to analyze the learning of the Chemistry pre-service teachers on chemical equilibrium identifying their difficulties to develop it, carried through in an Undergraduate Chemistry Course of a university. It was appealed to the qualitative research, with the analysis of questionnaires with opened questions, half-structuralized interviews and lesson plans done by the preservice teachers. To get the necessary data is was delimited as object of research, all of the 47 students registered in specifics subjects of Undergraduate Chemistry Course. The analysis of the data showed that the education of the topic about chemical equilibrium in the teachers formation is guided (for great part of the professors) by a conception that stimulates the mechanical way, reproductive, emphasizing much more the repetitive character than the potential to support the construction of concepts. According to the pre-service teachers reports, the professors unconsidered their previous knowledge and although this is a subject of High School, they need to deepen their knowledge in this area. The analysis of the questionnaires suggest that the students have difficulties with the conceptualization of the chemical equilibrium, the application of the rules of Le Chatelier and the equilibrium in watery way.